Disaster Intelligent Perception and Emergency Command of Power Grid - Yu, Zhen (Springer Nature, 2024)
This open access book addresses the current technical problems of low efficiency of emergency site information collection, lack of flexibility of emergency information interaction, lack of fusion analysis technology and disaster loss prediction model, and low intelligence of emergency auxiliary decision making. The content contains research on multiple information collection technology of power grid disaster loss, fusion analysis and prediction technology of power grid disaster loss information, and real-time information interaction technology between emergency site and command center in this work. This book illustrates the process of developing a prototype system for grid disaster perception and emergency command, which realizes the functions of grid disaster perception and emergency auxiliary decision-making and visualization command. The prototype intelligent perception and emergency command system for power grid disasters has been piloted in several units. It provided support for disaster loss prediction, disaster damage perception, and emergency command auxiliary decision-making in the earthquake in Sichuan, China, as well as the heavy rainfall in Zhejiang, China and Typhoon No. 9 "Lupi" that registered in Fujian, China, which significantly improved the emergency disposal Work efficiency.